THE IMPACT OF INTERGOVERNMENTAL FISCAL TRANSFERS ON LOCAL GOVERNMENT AUTONOMY AND SERVICE DELIVERY IN TANZANIA - Mtasigazya, Paul (PUPIL: International Journal of Teaching, Education and Learning, 2019)
A large part of the decentralization literature is fragmented along political, fiscal, or administrative lines. In this article, I employed a diagnostic framework to draw the dimension of fiscal decentralization reform through intergovernmental fiscal transfers and how the later has affected local government fiscal autonomy and performance on primary education service delivery in Tanzania. This study is broadly about fiscal decentralization reforms undertaken and implemented in local authorities in Tanzania with special focus to Dodoma Municipal Council. It aimed to find out the extent and manner the fiscal decentralization reform has been implemented and its effects on the council’s fiscal autonomy and performance in primary education service delivery. This study is based on data collected through questionnaire, focus group discussions and documentary review. The findings indicate that despite fiscal decentralization reform, still there has been no significant improvement in quantitative and qualitative primary education service delivery in the council. It was further noted that the practice of fiscal decentralization such as intergovernmental fiscal transfer,(grants) has not granted fiscal autonomy to local governments. The devolved funds also are characterized by conditional ties which undermine the autonomy and priorities of the Council. The study also noted that financial capacity of the council is weak despite the reform which have not provided for the expenditure on school infrastructure, furniture, teachers’ salaries, allowances and poor academic performance to standard seven examinations. The study further noted the challenges facing fiscal decentralization such as delay of funds, lack of transparency, corruption and inadequate funds disbursed to the council, have led to poor primary education service delivery in the Council in the long run. The study recommends that council should be assured of autonomy in fiscal control and management to ensure qualitative and quantitative primary education service delivery.